INVESTIGATING HOW SAP SOLUTIONS ASSIST IN WORKFORCE MANAGEMENT, SCHEDULING, AND HUMAN RESOURCES IN HEALTHCARE INSTITUTIONS - Surya Sai Ram Parimi (International Engineering Journal For Research & Development, 2019)
This work systematically explores the various roles and subsequent effects of SAP solutions in addressing and influencing the management of healthcare workforce. It goes a step further to explain how SAP contributes to the workforce and schedule management as well as the comprehensive range of human resource activities being practiced in healthcare organizations. Hence, while sifting through the carefully examined literature and referring judiciously to enlightening case studies, this research aims to unveil not only the real-life yields concerning palpable improvements in efficiency, but also philosophically assess the complex nature of the complexities and overall values resulting from the sound implementation of SAP solutions in healthcare environments. Therefore, by closely analysing the complexity of the system at SAP as a solution to workforce management in the healthcare industry, this study hopes to give the reader a realistic account of the impact of change that can be brought by the implementation of SAP solutions [1]. With the understanding of the complexity and nature of change that SAP brought to the issues of workforce management and scheduling precision and enhancement of the HR operations, this study was aimed at benefiting the healthcare administrators and the IT personnel. They are intended to contribute to the enhancement of the approaches, selected for the coordination of the personnel, in order to promote the development of the better systems of health care and ensure the increase of operational effectiveness within the framework of the healthcare organizations. Therefore, based on this research, the study hopes to shed light on ways of improving healthcare services with the help of carefully integrating SAP solutions in the management of the healthcare workforce. The utilities of implementing SAP solutions in the healthcare sector are evident as it marks a new way of handling workforce and resources by institutions [1,2]. Thus, by incorporating rigid ERP features into SAP with specific vertical applications in healthcare, institutions receive the capability to optimize their performance and increase workforce efficiency while focusing on prudent spending. Also, the accessibility of SAP solutions means that healthcare institutions, regardless of the size and level of development, can benefit from these solutions to address the challenges of the changing environment of healthcare delivery. Moreover, the SAP solution implementation in the healthcare context means not only the technological aspect but also the organizational one, including the change management and stakeholder management. Transforming the existing environment in healthcare institutions that are to implement SAP solutions involves changing processes, policies and competencies of human resources that correspond to the capabilities of the chosen SAP modules. In addition, cultivating the culture of the constant development and improvement of healthcare processes and ideas sustained by the SAP technology is just as essential to leverage the benefits of the SAP solutions in the management of healthcare workers. By integrating proper planning, teamwork, and adherence to excellence, various healthcare facilities can effectively manage the SAP solutions enhancing workforce management and organizational performance to improve the patients’ care results [2].